Life Cycle Assessment Applied to Green Building Certification in South Korea. (2015) - Gong, Yuri; Tae, Sungho; Suk, Sungjoon; Chae, Changu; Ford, George; Smith, Michael E.; Steffen, Robert
Abstract: The purpose of this study is to apply life cycle assessment (LCA) methodology for green building certification in South Korea. The method of environmental assessment in the field of building materials was examined using United States' LEED, and the United Kingdom's BREEAM building certification systems. Life cycle data and assessment methods were established on major categories of materials thorough theoretical consideration on life cycle assessment. Building materials, assembly methods, and building use considerations were used to develop an assessment model to evaluate the environmental performance of a building. Numeric values for use in the developed model were established for concrete, rebar, gypsum board, steel, cement brick, glass, and insulation materials to potentially reduce greenhouse gas (GHG) emissions by 95% or more. An assessment method and LCA database were established. The model will be used to show that the choice of building materials can affect the GHG emissions during the construction phase of a building.